Perancangan Sistem Informasi Monitoring dan Reporting Program Pemberdayaan dan Kesejahteraan Keluarga (Studi Kasus: Kelurahan X) - Maharani, Herastia; Fiarni, Cut; Mulyani, Shinthia (Yayasan Petra Harapan Bangsa, 2018)
PKK is a movement that aims to empower families to improve people's welfare. PKK has 10 main programs, consisting of Understanding and Practicing Pancasila, Gotong Royong, Food, Clothing, Housing and Housekeeping, Education and Skills, Health, Development of Cooperative Life, Environmental Sustainability, Healthy Planning. The PKK strategy to reach as many families as possible is carried out through the